18F FDG PET-CT for EBRT Planning in Inoperable Rectal Carcinoma after Receiving Chemotherapy– A - Begum, Shamim MF; Begum, Fatima; Hossain, Raihan; Siddique, Md Abu Bakker; Nath, Khokon Kumar; Hasan, Mizanul (Bangladesh Journal of Nuclear Medicine, 2018)
Colorectal cancer (CRC) is the third most commonly diagnosed cancer in men and the second in women globally. The incidence varies with geographic difference. In Bangladesh, hospital based cancer registry shows rate of CRC in male 10.1%- 12% and in female 3% - 12.0%. The prognosis of the disease and treatment planning depends upon the staging of the disease. Surgery is usually a common way of treatment of rectal cancer except some cases with advanced stage. Radiation therapy, often with chemotherapy, is frequently used in the adjuvant or neoadjuvant setting for the treatment of rectal cancers. External beam radiation therapy (EBRT) is a well practiced method of treatment in the in-operable cases of rectal cancer. 18F FDG PET-CT is a well recognized imaging tool in the pretreatment evaluation of colorectal cancer worldwide. Accurate staging is needed for proper selection of treatment and cost effectiveness. Here, we discussed a case of rectal cancer (stage IV) with post chemotherapy state with history of palliative loop iliostomy bypass. The patient was referred for 18 F FDG PET-CT scan for restaging of the disease and to localize functioning tumor site for external beam radiotherapy (EBRT) planning. FDG PET-CT imaging revealed FDG avidity at the primary tumor site, perircetal fat and multiple FDG avid hypermetabolic lymphnodes in pelvic cavity. A focal FDG avid lesion in anterior aspect of liver suggests hepatic involvement. The fusion PET-CT imaging has played an important role in the further management of the patient by providing guidelines in EBRT. Bangladesh J. Nuclear Med. 19(1): 56-60, January 2016